Effects of Gasoline and Hydrogen Blends on Exhaust Gas Emissions and Fuel Consumption from Gasoline Internal Combustion Engines - Merlin Zacharie Ayissi; Ivan Aquigeh Newen; Rhiad Alloune; Dieudonné Bitondo (Journal of Combustion)
Gasoline engines remain a potential source of atmospheric pollution. Dual fuel combustion was under investigation to cope with exposure to pollutants. Investigations on emission parameters and engine performance for a single-cylinder four-stroke petrol engine are carried out using multicriteria decision-making method (MCDM). Bar charts are constructed for three emission parameters in function of engine temperature and fuel consumption for different blends. Fuels were supplied at different engine running speeds. Parameters recorded during the experimental study were the concentrations of carbon monoxide (CO), hydrogen sulfide (H2S), percentages of lower explosive limit (LEL), and combustion duration. The maximum concentration of CO was 339 ppm at 70°C and 4000 rpm. The maximum concentration of H2S (3 ppm), was recorded at 94°C and 4000 rpm. The maximum percentage of LEL recorded was 3% at the majority of temperature and 4000 rpm. Consumption of 25 Cl of (gasoline + HHO) was recorded during the maximum time (50 min). The experiment showed high emissions of CO that can provoke respiratory disorders and explosive gases, factors of explosion at high speeds (4000 rpm), and low temperature (70°C). H2S emissions are very low (0–3 ppm) independently of the engine speeds and temperature. Blending gasoline with HHO shows a reduction in fuel consumption.